A mass stranding of seven Longman's beaked whales (Indopacetus pacificus) in New Caledonia, South Pacific. Issue 3 (3rd February 2016) - Garrigue, Claire; Oremus, Marc; Dodémont, Rémi; Bustamante, Paco; Kwiatek, Olivier; Libeau, Geneviève; Lockyer, Christina; Vivier, Jean Christophe; Dalebout, Merel L.
Abstract: Seven Longman's beaked whales ( Indopacetus pacificus ) stranded together in southern New Caledonia on 16 November 2013 (one adult male, two adult females, two subadult females, one calf, and one unknown). At this time, we have no evidence to suggest that this event was an "atypical" mass stranding associated with active naval sonar or other anthropogenic activities. The adult females were slightly larger (618–640 cm) than the adult male (590 cm). The length of the calf ( ca . 300 cm) suggests it was less than a year old. Five of the whales were sampled for mitochondrial (mt) DNA analysis to confirm species identification. All shared the same haplotype over 680 bp of the mtDNA control region. High concentrations of Hg, Fe, Se, Zn (all in the liver), and Cd (in the kidneys) were detected. Necropsies revealed plastic debris in the stomach of two of the whales. One of these same whales had chronic gastritis while the other had acute pleurisy and also tested positive for morbillivirus. This infection may have been a major factor behind this mass stranding event.